Effect of Different Regional Climates on Persimmon Quality - Saeid Shiukhy Soqanloo (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2015)
Persimmon (Diospyros kaki) is grown in wide climate conditions, which may affect fruit biochemical characteristics such as vitamins, soluble solids and antioxidants. Therefore, the aim of this research is to evaluate the biochemical responses of fruit to these climate variables. For this purpose 5 districts of Kashan, Shahrud, Yazd, Kiasar and Sari were chosen to collect fruits. On November 2012, based on a complete block design ripen fruits were collected and quality factors were measured. The results of this research showed that local climate condition significantly (P < 0.01) influenced fruit biochemical characteristics. Fruit collected from Kashan had the highest vitamin C (1.74 mg /100 ml) acidity (pH = 6.6), while the samples from Shahrud had the highest soluble solids (22.13) and titratable acidity (0.04 mg/100 ml). Fruits collected from Yazd showed significant differences in Chl- and carotenoids contents, 0.07 and 0.42 mg/g, respectively, relative to other sites. These results show that arid and semi-arid districts enhance fruit quality.